Profiling multi-enzyme activities of Aspergillus niger strains growing on various agro-industrial residues - Laothanachareon, Thanaporn; Bunterngsook, Benjarat; Champreda, Verawat (3 Biotech, 2022)
Agro-industrial wastes provide potential sources of carbon for production of fungal enzymes applied for various biotechnological applications. In this study, 23 strains of Aspergillus niger were systematically investigated for their capability on production of carbohydrate-processing enzymes used in industries. The strains were grown on glucose or selected agricultural wastes comprising varied chemical compositions as the sole carbon source. As a control, glucose induced basal activities of amylase, pectinase, and xylanase in only a few strains, while the CMCase, β-glucanase, and invertase activities were detected only when the carbon source was switched to the agro-industrial biomass. According to one-way ANOVA analysis, banana peels containing lignocellulosic components with high pectin and starch contents with its easily digestible nature, were found to be the best carbon source for inducing production of most target enzymes, while the cellulose-rich sugarcane bagasse efficiently promoted maximal levels of β-glucanase and xylanase activities. The starch fiber-rich cassava pulp also effectively supported the activities of amylase and most other enzymes, but at relatively lower levels compared to those obtained with banana peel. The A. niger TL11 strain was considered the most potent strain for production of all target enzymes with the CMCase, xylanase, pectinase, β-glucanase, amylase, and invertase activities of 76.15, 601.59, 160.89, 409.20, 426.73, and 1186.94 U/mL, respectively. The results provide insights into the efficiency of various carbon sources with different chemical compositions on inducing the target enzymes as well as the dissimilarity of A. niger strains on the production of different carbohydrate-processing enzymes.